Association of AID and MUM1 by Immunohistochemistry in Diffuse Large B-Cell Lymphoma - Mardiah Suci Hardianti; Syahru Agung Setiawan; Nungki Anggorowati; Wiwiek Probowati (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Diffuse large B-cell lymphoma (DLBCL) is a heterogeneous disease with dysregulation of somatic hypermutation (SHM) and class switch recombination (CSR) have been known to contribute for its lymphomagenesis. Activation-induced cytidine deaminase (AID) enzyme plays a vital role for both processes. Multiple myeloma oncogene 1 (MUM1) is known to upregulate the AID expression in normal and pathological conditions. However, both AID and MUM1 expression association in DLBCL is still unexplored using immunohistochemistry method. We examined DLBCL samples and then retrospectively tested its correlation with clinical findings.METHODS: A retrospective cohort study with 20 cases of DLBCL biopsy tissue with AID and MUM1 antibody was conducted. The samples were then classified into concordant (AID+/MUM1+ or AID-/MUM1-) and discordant group (AID-/MUM1+). The clinicopathological comparison was performed to observe any association between immunohistochemistry expression and clinical findings.RESULTS: Among 20 samples of DLBCL, concordant expression rate of AID and MUM1 was 80% with kappa Cohen’s of 0.578 (p=0.004). A significant association was observed between AID and MUM1 expression with a prevalence ratio of 2.25 (95% CI: 1.08-4.67; p=0.008). Clinical characteristics were not significantly different between each group. Restricted mean survival time was shorter in the concordant group compared with the discordant group but statistically insignificant (21.16 vs. 22.5 months; p=0.531).CONCLUSION: The result of this study showed the association between AID and MUM1 expression in DLBCL. However, whether the association may add further molecular heterogeneity of DLBCL is still to be confirmed by expanding the study.KEYWORDS: AID, CSR, DLBCL, MUM1, SHM